RESOLUSI KONFLIK HUBUNGAN INDUSTRIAL DALAM SISTEM PENYELENGGARAAN KETENAGAKERJAAN DI KABUPATEN PASURUAN - Heri Sunarno; Khafizh Rosyidi; Aris Setiawan; Hambali Hambali (STIE Mahardhika, 2019)
National development in the labor sector that includes related elements between government, employers and workers is felt necessary to base their interests on their respective principles, so that dynamic industrial relations will be created, but the dynamics of industrial relations in Indonesia have recently been marked by the problem of lack - harmony between the entrepreneur and his workers. The government as the main sector in industrial relations must act based on the provisions of legal products from the industrial relations sector so that the PPHI process can be realized in accordance with the expectations of all parties. In the context of maintaining industrial relations in Pasuruan, regulations in the form of Regional Regulation No. 22 of 2012 concerning the employment system has been created. It is hoped that through this research, an easy-to-understand resolution model that illustrates efforts to resolve industrial relations disputes in accordance with Regional Regulation No. 22 of 2012. And this research is expected to produce a model of industrial relations conflict resolution which is the development of the Marshall model by considering the history of conflict through a picture of the birth of a particular conflict